Алгебра, вопрос опубликован 04.03.2019 00:52 annavilnitskaja

X^2 - (x+3)(x-3)=3x (2x-1)^2-4(x-2)(x+2)=0 решите уравнение

Ответы
Ответ добавил: Гость

x+y+z=496

y=8x/15 

x=z/(2 3/5) 

 

x+y+z=496

y=8x/15

z=13x/5 

 

x+8x/15+13x/5=496 |*15

15x+8x+39x=7440

62x=7440

x=120

 

y=8*120/15

y=8*8

y=64

 

z=13*120/5

z=13*24

z=312

 

 

 

Ответ добавил: Гость

а) x^3 - 7 = -27,  x^3 = -20      может

б) x^3 - 7 = 34,    x^3 = 41    может

в) x^3 - 7 = 132,  x^3 = 139    может

г) x^3 - 7 = -64,    x^3 = - 57    может

Ответ добавил: Гость
1) 1.x²-x²+9=3x.2. 3x=9.3. x=3.2) 1. 4x²-4x+1-4x²+16=0.2. 4x=17.3. x=17/4.4. x=4,25.
Больше вопросов по алгебре
Предмет
Алгебра, опубликовано 18.03.2019 20:30